DOES THE USE OF SOCIAL MEDIA AND MOTIVATIONAL SOURCES AFFECT LEARNING ACHIEVEMENT? REFLECTIONS ON THE LEARNING SYSTEM OF JUNIOR HIGH SCHOOL STUDENTS IN THE PANDEMIC PERIOD - Rulindova, Alia Athaya; Mardhatillah, Amy; Rulindo, Ronald (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
This study examines the impact of social media and motivational sources on learning achievement during the pandemic among junior high school students. The research specifically analyzes the effects of intrinsic and extrinsic motivation, as well as the role of social media in providing support for learning.Using a quantitative approach, data were collected from 327 students through questionnaires and analyzed via regression analysis. The results indicate that intrinsic motivation significantly influences learning achievement (B = 0.135, t(198) = 5.150, p < .001), while extrinsic motivation also has a significant effect (B = -0.057, t(198) = -2.090, p = .037). However, the hypothesis regarding social media as a supporting infrastructure for learning did not yield significant results (B = 0.031, t(198) = 0.399, p = .690). In contrast, social media's role in providing social support positively impacted learning achievement (B = 0.209, t(198) = 2.567, p = .011). No significant relationship was found between gender and academic achievement (B = 0.103, t(198) = 0.328, p = .743).The regression model explained 18% of the variance in learning achievement, indicating that additional factors may influence academic success. These findings highlight the importance of fostering intrinsic motivation and suggest that educational institutions should implement strategies to enhance students' intrinsic motivation, such as engaging learning activities and supportive environments. Furthermore, schools should leverage social media as a tool for providing social support, which can enhance learning outcomes. Future research should explore effective programs aimed at increasing intrinsic motivation to ensure sustained academic achievement utilizing online learning approaches.